Time-resolved luminescence spectroscopy study of CsI:Eu crystal - Yakovlev, V.; Trefilova, L.; Karnaukhova, A.; Ovcharenko, N.; Kisilc, E. (Functional Materials, 2013)
This paper studies the spectral-kinetic properties of CsI:0.8·10⁻⁴ % Eu, CsI:1·10⁻² % Eu and CsI:3.9·10⁻¹ % Eu crystals. It has been found that spectrum and decay kinetics of photoluminescence depend on concentration of an activator and degree of thermal-dynamic disbalance of CsI:Eu. The emission of all the crystals decays exponentially, but each crystal differs from each other in temperature behavior of the emission decay kinetics. Possible types of the emission centers have been suggested such as single dipole Eu²⁺–vc, two- and three-dipole clusters of Eu²⁺–vc– which are responsible for the bands with maxima at 2.69, 2.78 and 2.67 eV, respectively. Criterion for discrimination of the emission centers in CsI:Eu is the temperature behavior of their emission decay kinetics.